Specificity and Sensitivity of Screening for Anti-HLA Antibodies in Kidney Allograft Dysfunction - Viana, H (2012)
BACKGROUND: Prospective testing for posttransplant circulating anti-HLA antibodies seems to be a critical noninvasive tool, but confirmatory data are lacking. MATERIALS AND METHODS: Over the last 3 years, peritubular capillary (PTC) C4d deposition was prospectively sought by an immunofluorescence technique applied to frozen tissue in biopsies obtained for allograft dysfunction. Screening for circulating anti-HLA class I/II alloantibodies (AlloAb) by the flow cytometric test was performed simultaneously. RESULTS: We evaluated 132 sets of biopsies and simultaneous serum samples. PTC C4d deposition was demonstrated in 15.9% (21/132) of biopsies. Circulating anti-HLA I/II AlloAb were detected in 25% (33/132) of serum samples. Employing receiver-operator characteristic (ROC) curves for all C4d-positive biopsies, screening for AlloAb showed a global specificity of 82% and sensitivity of 61.9%. When this analysis was restricted to biopsies obtained in the first month posttransplantation, the sensitivity increased to 81.8%, but the specificity decreased to 76.9%. After the first month posttransplantation, we observed sensitivity of 40.0% and a specificity of 86.4%. In the first month posttransplantation, all patients with a diagnosis of acute antibody-mediated rejection displayed circulating anti-HLA class I/II, but not always at the same time as the C4d-positive biopsy. CONCLUSIONS: In the first month posttransplantation, prospective monitoring of anti-HLA antibodies may be useful. The high sensitivity allows the identification of patients at risk, affording an earlier diagnosis of antibody-mediated rejection. After the first month, the test can be used to evaluate allograft dysfunction episodes, since positivity is highly suggestive of an antibody-mediated process.